Inhibition of Lincpint expression affects insulin secretion and apoptosis in mouse pancreatic β cells. (November 2018) - Zhu, Yanan; Li, Yihui; Dai, Chengting; Sun, Lu; You, Lianghui; De, Wei; Yuan, Qingxin; Wang, Ning; Chen, Yuanyuan
Abstract: LncRNAs have been reported to maintain islet function and are associated with the development of diabetes. Here, we investigated Lincpint biological functions in mouse pancreatic β cells both in vivo and in vitro. We observed that Lincpint was highly expressed in BALB/c mouse islets and downregulated in db/db mouse islets by using qRT-PCR. Lincpint could be regulated by different concentrations of glucose in MIN6 cells. MTT and flow cytometry showed that silencing Lincpint expression in vitro increased cell apoptosis. In a GSIS assay, we detected that inhibition of the expression of Lincpint suppressed insulin synthesis and secretion. In male BALB/c mouse, blood glucose and serum insulin were decreased after knockdown of Lincpint expression as detected by IPGTT and ELISA. Immunohistochemistry indicated that positive islet area and expression of Pdx1 and Glut2 was reduced after Lincpint silencing in male BALB/c mouse. These findings suggest that Lincpint may play an important role in maintaining islet β cell function and is worthy of further investigation due to its potential in diabetes treatment.